Modelagem de alta resolução para estimativa do potencial eólico offshore da costa do Ceará - Lima, Danielle Kely Saraiva de (2015)
The technology for conversion into electricity of onshore wind energy is rather consolidated; the challenge now is to make the offshore exploitation to follow the same course. The European Union produces offshore wind power since 1991, exceeding 9 GW of installed power at the end of 2014. Brazil, on the contrary, does not have any offshore wind power plant and there are few studies in this direction. The exploitation of wind power production requires as a premise the knowledge of the profile of the wind in the region of interest. The objective of this thesis is to apply a methodology able to estimate the offshore wind potential of the coast of the State of Ceará, in Brazil, through the study of characteristic years marked by the presence of the El Niño and El Niña phenomena in periods considered extremes, dry and wet. An investigation using the mesoscale numerical model RAMS (Regional Atmospheric Modeling System) was performed, with resolution of 2 km, taking into consideration periods with presence of El Niño and La Niña phenomena, as well as a Neutral year with the absence of these phenomena. The simulation results presented the maxima and averages of wind speed and the prevailing wind direction on the coast of the State of Ceará. The microscale model WAsP (Wind Atlas Analysis and Application Program) was used for the evaluation of microsites of four case studies along the coast of Ceará. The chosen cities were Icapuí, Lagoinha, Camocim and Flecheiras, located in different regions along the coast of Ceará, for which they were presented the Weibull distribution, power density, wind speed and the energy production of each area. The results indicated an average wind speed above 8 m/s in the dry season, in the three evaluated periods. The direction of the prevailing wind in the dry season was from East to West and the turbulence intensity was lower in the dry season of El Niño year. It was found that the eastern coast of Ceará has the highest rates of average and maximum wind speed. Camocim, the city representing this region, presented a capacity factor in the neutral year of 57.49 %, above the figures found to the other cities analyzed. The annual energy production of an estimated wind power plant of 90 MW in Camocim, with capacity factor of about 50%, exceeded 400 GWh. Bathymetry of the State of Ceará is shallow and large ships travel at a considerable distance from the coast.